PENGARUH PELAYANAN AKADEMIK TERHADAP TINGKAT KEPUASAN MAHASISWA UNIVERSITAS BANTEN JAYA (UNBAJA) - Khristina Sri Prihatin; Yohana Selvia Dewi (Progress: Jurnal Pendidikan, Akuntansi dan Keuangan, 2019)
This research was conducted at University Banten Jaya (UNBAJA). The purpose of this research were: 1) to know how the quality of academic service. 2) to know how student satisfaction. 3) to know how the influence of academic service to the level of student satisfaction. In this research data collection technique was spreading questionnaires for 322 respondents(19,5%) of 1.649 populations. The method used in this research was descriptive. The Data analysis included, validity test, reliability test, classical assumption test (residual normality, heteroscedasticity, linearity), correlation analysis, simple linear regression analysis, significance test (f test, t test,coefficient of determination). The results were data analysis has been done obtained results where the academic services included into the category of "High Service Quality" (62,28%). Meanwhile, the level of student satisfaction "Satisfied" category (0,81). And the influence of academic service to the level of student satisfaction was 0,678, it meant that the influence of Academic Service (X) on Student Satisfaction Level was 67,80% and 32,2% was influenced by other variable. Thus it could be concluded that there was significant influence between the academic service on the level of student satisfaction.